Inflation and growth in the WAMZ: Evidence from a threshold analysis - Abu Bakarr Tarawalie; Momodu Sissoho; Mohamed Conte; Christian R. Ahortor (West African Monetary Institute (WAMI), 2012)
The focus of this paper was to empirically estimate the threshold levels of inflation in the WAMZ, using the conditional least square technique. The study also identified the determinants of growth in the WAMZ. The empirical analysis uses annual data from 1970-2010 for Ghana, Nigeria and Sierra Leone, and 1980-2010 for the Gambia and Guinea. The results showed that there exists a statistically significant long-run negative relationship between inflation and economic growth for the WAMZ countries. Furthermore, the empirical results strongly suggest the existence of threshold level of inflation for the WAMZ countries, beyond which inflation exert a negative effect on growth. The results revealed an inflation rate of 9 percent as the optimal rate of inflation for the WAMZ countries. The results showed that WAMZ countries threshold inflation rates lie within the convergence criterion of maintaining an inflation rate not exceeding 10 percent. The results are useful for policy makers in providing some clue in setting an optimal inflation target. Policy makers should implement policies aimed at achieving the threshold inflation rate that is consistent with higher economic growth. Thus, it is desirable to keep inflation rate at least within the threshold level in member countries, as it may help maintain sustainable growth. A sustainable increase in growth can be achieved by directing monetary policy towards maintaining price stability.
Keywords: 330; Inflation rate; Real GDP; threshold effect; WAMZ countries; Conditional least square